Drinking Coffee and Learning Approach, Not Learning Style, Support Medical Students' Block Completion - Fithriyah, Saidatul; Nafasadila, Fatma; Pramuningtyas, Ratih; Sintowati, Retno (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This research was conducted to determine and analyse the relationship between drinking coffee, learning styles, and approaches with block completion in medical students. Methodology: The research method used was observational analytics with 80 third-year students of the Faculty of Medicine, Universitas Muhammadiyah Surakarta (FK UMS), Sukoharjo, Central Java, Indonesia as the samples. Purposive random sampling was used to select samples who met the restriction criteria. To identify relationships and influences between variables, the collected data was analysed using Chi-square test with the alternative Fisher exact test and logistic regression test. Results: There was a significant relationship between drinking coffee (p=0.012) and learning approach (p=0.001) with block completion, but not between learning style with block completion (p=0.594). Learning approach had a stronger relationship. The probability of block completion reaching 98.4% if students drink coffee and use a deep learning approach to prepare for the block exam. Applications/Originality/Value: Drinking coffee and applying a deep approach to learning, support a greater block completion rate.